The modulatory action of C-Vx substance on the immune system in COVID-19 - Tahrali, Ilhan; Akdeniz, Nilgun; Yilmaz, Vuslat; Kucuksezer, Umut C.; Oktelik, Fatma B.; Ozdemir, Ozkan; Cetin-Aktas, Esin; Ogutmen, Yelda; Ergen, Arzu; Abaci, Neslihan; Tuzun, Erdem; Oncul, Oral; et al. (TAYLOR \& FRANCIS LTD, 2022)
The modulatory effect of C-Vx, a novel therapeutic agent, on the immune system of COVID-19 patients was investigated. The functions of T and NK cells of COVID-19 patients with different disease severity were evaluated by flow cytometry in response to C-Vx stimulation. The levels of pro- and anti-inflammatory cytokines were detected by multiplex assay in supernatants after cell culture with C-Vx. Bradykinin, IRF3, and IFN-alpha levels were also measured by ELISA in the presence or absence of C-Vx stimulation. As a result, increased CD107a expression was observed on NK cells in response to C-Vx addition. The proliferation of T cell subsets was increased by C-Vx, decreasing by disease severity. IL-4 and IL-10 levels were elevated while IFN-gamma and IL-17 levels were reduced in T cells following C-Vx stimulation. However, the levels of pro-inflammatory IL-1 beta, IL-6, IL-8, IFN-gamma and GM-CSF were significantly increased upon C-Vx stimulation. IFN-alpha levels tended to increase after incubation with C-Vx. These findings support an immunomodulatory action of C-Vx on the immune system of patients with a mild and moderate phase of COVID-19.
Keywords: C-Vx; COVID-19; cytokines; cytotoxicity; immune system; inflammation; lymphocytes; proliferation